Daily Usage of Proton Pump Inhibitors May Reduce the Severity of Critical Upper Gastrointestinal Bleeding in Elderly Patients - Hidetaka Matsuda; Takuto Nosaka; Yu Akazawa; Yasushi Saito; Yoshihiko Ozaki; Kazuto Takahashi; Tatsushi Naito; Kazuya Ofuji; Masahiro Ohtani; Katsushi Hiramatsu; Yasunari Nakamoto (Gastroenterology Research and Practice)
Introduction. We retrospectively examined the relationship between daily proton pump inhibitor (PPI) use and severity of upper gastrointestinal bleeding (UGIB), mainly in the elderly. Methods. We included 97 patients with nonvariceal UGIB diagnosed at our hospital from January 2012 to October 2017. Bleeding severity was assessed using the shock index (SI) and estimated bleeding volume; 49 patients met the criterion for the mild group and 48 for the moderate/severe group. The effect of PPI use on bleeding severity was compared between the groups. The relationships of PPI use and dose with the clinical symptoms of UGIB were also analyzed. Results. Among the 97 patients, 17 (17.5%) habitually used PPIs. The rate of habitual PPI use was significantly higher in the mild group, indicating as an independent factor contributing to a reduction in the severity of UGIB in a multiple logistic regression analysis (30.6% vs. 4.2%; OR 10.147; 95% CI 2.174–47.358, P<0.01). When analyzing data for a subgroup of patients older than 75 years, we found the protective PPI effect to be even higher in the mild UGIB group than in the moderate/severe group (37.0% vs. 5.6%; OR 10.000; 95% CI 1.150–86.951, P<0.05). Conversely, we found no association between PPI prescription and UGIB symptoms in patients younger than 75 years. The mean estimated bleeding volume and SI in the 17 habitual PPI users were both significantly less than those among the 80 nonhabitual users, respectively (P<0.05). The proportion of patients with mild UGIB was similar between the low- and high-dose PPI users. Conclusions. Particularly in elderly patients with nonvariceal UGIB, habitual PPI use can alleviate the clinical symptoms of UGIB by suppressing the volume of bleeding, regardless of the adapted dose of PPIs.